2012
DOI: 10.1186/1479-5868-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sedentary time and physical activity in workplace and non-work contexts: a cross-sectional study of office, customer service and call centre employees

Abstract: BackgroundTo examine sedentary time, prolonged sedentary bouts and physical activity in Australian employees from different workplace settings, within work and non-work contexts.MethodsA convenience sample of 193 employees working in offices (131), call centres (36) and customer service (26) was recruited. Actigraph GT1M accelerometers were used to derive percentages of time spent sedentary (<100 counts per minute; cpm), in prolonged sedentary bouts (≥20 minutes or ≥30 minutes), light-intensity activity (100–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
328
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(382 citation statements)
references
References 42 publications
25
328
2
11
Order By: Relevance
“…Beginning work was also associated with decreased ST in the young women, a finding which may reflect a transition to jobs such as nursing, teaching, service etc., which typically have lower ST than managers and office workers (Thorp et al, 2012, Jans et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning work was also associated with decreased ST in the young women, a finding which may reflect a transition to jobs such as nursing, teaching, service etc., which typically have lower ST than managers and office workers (Thorp et al, 2012, Jans et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The shift away from the workplace, which often involves high ST (Jans et al, 2007, Miller and Brown, 2004, Thorp et al, 2012, may allow more time for active leisure pursuits in retirement. This is supported by the findings from a previous ALSWH study which showed that retirement was associated with increases in moderate and vigorous PA (Brown et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accurate and proper assessment of occupational physical activity is an important but challenging task for health researchers [5]. In particular, it is difficult to assess light intensity physical activity via self-report, but such activity may have important health implications for workers if it replaces long hours spent to perform sedentary tasks [6][7][8]. In contrast to subjective assessment through self-report, use of individual monitors, such as pedometers or armbands, may provide an objective measure of human behavior.…”
Section: Materials and Methods Participants And Overview Of Proceduresmentioning
confidence: 99%
“…Studies using accelerometer have shown Australian adults to be sedentary for an average of 57% of their waking hours, corresponding to just over 9 hours per day (12), while US adults were sedentary for 7.3-7.9 hours per day, depending on age (13). For many people of working age, a considerable part of the total sedentary time on a workday occurs during working hours (14,15). Thus, too much sitting and too little PA during working hours has been raised as an emerging major public health concern by several authors (16)(17)(18), and recommendations have been proposed to ensure sufficient PA at work (19).…”
mentioning
confidence: 99%